The role of individual physical body measurements and activity on spine kinematics during flexion, lateral bending and twist tasks in healthy young adults – Comparing marker(less) data. (April 2023) - Sharma, Harsh; Karan, Supreeth S.; Kumari Agrawal, Ayushi; Vemuri, Kavita
Highlights: Range of Motion(ROM) analysis of the inter-intra motion of each segment of the spine. A simple and effective local coordinate system to extract the relative orientations of each segment of the spine. Physical activity significantly correlates to ROM in young healthy adults. The model generated is reference for clinical diagnosis. Abstract: Understanding the relationship between physical characteristics and activity to kinematic properties of the spine has implications for sports, occupational tasks, clinical diagnosis and prognosis. This study aimed to categorize spine kinematics from flexion, lateral-bend, and twist exercises by examining the correlations to body-mass index (BMI), waist-to-hip ratio (WHR), and physical activity levels in healthy young adults. The data was collected from a marker-based optoelectronic motion capture setup and a marker-less motion capture with the RGB camera of a standard mobile phone. Comparing the accuracies of the two techniques on the same data set is important to develop inexpensive (RGB camera) diagnostics. Sixty-two participants (40 Male, 22 female) participated in the study. The angular displacement of the spine for each exercise was extracted by vector analysis using a single reference node/marker. The analysis showed no significant correlations of angular displacements values for the three movements with BMI or WHR. The physical activity level of male participants is significantly correlated with angular displacements for the flexion (p < 0.001) and lateral-bend (p-value ranges from 0.001 to 0.04) and weakly correlated (but not significant) for twist exercises. The physical activity level shows a significant correlation for only flexion (p < 0.001) in female participants. The findings emphasize the critical role of physical activity on musculoskeletal flexibility in young, healthy adults. The angles estimated using both techniques were comparable and significantly correlated across participants and exercises.